Fresamento de canais da liga de alumínio aeronáutico 7075-T7 - Suarez, Mauro Paipa (2008)
Every single design of manufacturing by conventional machining targets a finish part with ideal dimensions within acceptable tolerances. The smaller the tolerances the higher the machining time and the costs involved. In order to reduce costs it is interesting to obtain higher accuracy and better surface finishing with only one machining process. The heat generated during machining is dissipated through the parts involved (chip, tool, workpiece and atmosphere) and the distribution depends on the cutting conditions, mainly on the cutting speed. The relationship between the heat generated and dissipated is known as energetic balance. If the heat dissipated through the workpiece is reduced, the thermal expansion will also be diminished and therefore the dimensional accuracy will be higher. The main objective of the present work is to evaluate the influence of the cutting parameters (vc, fz, ap), the distance among the slots opened and the cooling-lubrifying system (MQL, Dry and overhead flood cooling) on the dimensional accuracy and on the surface roughness of 7075 - T7 aerospace aluminium alloy workpieces (heat treated Al-Zn-Mg alloy) when end milling small slots with integral cemented carbide tools. The experimental tests carried out following a Design of Experiment (DOE) and the results were based on Variance Analysis Technique (ANOVA) with 95% of confidence. The temperature of the bottom surface of the slots and the workpiece vibration controlled by an infrared sensor and an accelerometer, respectively. Surface response method and minimum square techniques were used for the optimization process. The results showed that among the in-put variables only the cutting fluid applied in the MQL manner improved the dimensional accuracy. The feed rate has had great negative influence on the surface roughness of the slots and high cutting speeds has reduced it. The workpiece temperature was diminished when the feed velocity was increased. The power consumption and vibration of the system increased proportionally with the increase of cutting speed and deep of cut.